Aplicação de sistema nanoestruturado como estratégia para proteção de compostos bioativos de jambo vermelho (Syzygium malaccense) em formulações cosméticas - Dambros, Talia Rebelatto (2024)
As we age, concerns about premature aging influenced by environmental factors and oxidative stress increase. This leads to a search for cosmetics that prevent and repair skin damage while keeping it healthy and protected. In light of this, red jambo extract emerges as a promising and natural source of antioxidants. However, many natural compounds are chemically unstable, making them prone to reactions that reduce their efficacy over time. In response, this study introduces a technological innovation by developing an anti-aging cosmetic formulation rich in antioxidant flavonoids extracted from the leaves of red jambo (Syzygium malaccense), combined with nanostructured hydroxyapatite as a strategy to protect the bioactive compounds. The antioxidant potential was evaluated through DPPH and ABTS radical scavenging assays, ferric reducing antioxidant power (FRAP), total phenolic compounds (TPC), and the identification and quantification of phenolic compounds by high-performance liquid chromatography with diode-array detection (HPLC-DAD), as well as minimum inhibitory concentration (IC50). Hydroxyapatite was characterized both in its pure form and when impregnated with the extract, using transmission electron microscopy (TEM), X-ray diffraction (XRD), dynamic light scattering (DLS), and Fourier-transform infrared spectroscopy (FTIR). Ingredient concentrations for the formulations were determined using qualitative exploratory studies followed by factorial design. The formulations underwent accelerated stability testing for 12 days, where organoleptic properties (color, odor, appearance), physicochemical properties (pH, density, centrifugation, spreadability), IC50, and rheological behavior in steady and oscillatory regimes were evaluated. Finally, a sensory evaluation was conducted using the ideal profile method (IPM). The results showed good antioxidant capacity of the red jambo extract, with 333.54±7.0 mg GAE.g-1 (TPC) and an IC50 of 40.733 mg.mL-1, and excellent efficiency of hydroxyapatite (HA) application as a protective agent for the bioactive compounds, with an increase in IC50 value from 33.71 to 39.30 mg.mL-1. HPLC-DAD analysis identified and quantified compounds such as gallic acid, myricitrin, and myricetin. Concentrations of hydroxyethylcellulose, hyaluronic acid, and extract were set at 0.1%, 1%, and 0.5%, respectively. Factorial design indicated that the content of hydroxyethylcellulose is directly proportional to viscosity and turbidity, and hydroxyethylcellulose and HA (containing extract) is inversely proportional to antioxidant activity. Formulations were characterized rheologically in a steady state as non-Newtonian fluids with shear-thinning viscosity and in an oscillatory regime as diluted solutions with a predominance of viscous forces over elastic forces. The odor and appearance remained stable during the stability study. The color of the extract-free sample underwent significant changes, while the HA impregnated with extract (HAext) underwent slight modifications. The pH remained between 5.00 and 6.00, suitable for skin. Density and spreadability remained stable. All cosmetic formulations, including HAext, showed good acceptance and met consumer expectations. Therefore, this study provides important information about the bioactivity of compounds from the leaves of S. malaccense, with novel results for their application in facial serum cosmetic formulations.